Rebirth of left radial artery access: could this be the 'right' radial artery?. (June 2015) - Taylor, Montoya; Capers, Quinn; Patel, Dilesh; Mehta, Nishaki K
<x xml:space="preserve">Abstract</x> Cardiac catheterization has several risks, notably which include bleeding, stroke and death. The transradial (TR) approach to catheterization is associated with a lower bleeding risk. The right radial approach is the default method in most laboratories and the left radial artery (LRA) serves as the bail-out approach. This article discusses the advantages and disadvantages of transfemoral and TR access routes. The authors envisage an increased adoption of the LRA approach, due to the anatomical superiority and ease of catheter engagement afforded by this approach. The authors discuss ways to increase operator ease for LRA in the laboratory and propose a novel way to improve LRA work-flow.